The Development Of Multimedia-Based Digital Simulation E-Book For Vocational Schools - Nurhikmah H; Arnidah Arnidah; Hamsar Hasfat (Journal of Educational Science and Technology (EST), 2021)
This research is development research aimed to develop a learning product in the form of a Multimedia-based E-book on Digital Simulation Subjects which are feasible or valid and easy to use or practical. The test subjects in this research and development consisted of content experts, media experts and subject teachers of digital simulation and grade 10th students of SMK Negeri 4 Gowa. The ADDIE development model used in this study consisted of five stages, namely: (1) analysis stage, (2) design stage, (3) development stage, (4) implementation stage (5) evaluation stage. The development of  multimedia-based digital simulation e-book through the material expert validation stage with the score of 4.73 and media validation 4.60 shows that the material and design or media evaluation in the e-book is feasible or valid. Then, the teacher's response obtained a score of 4.71, the average score of individual student trials was 92.14, and the average score of the student group trial was 90, which means the e-book is easy to use by teachers and students. there were no students who acquired a low score from the test results after learning using the e-book which means it is effectively used.